1996
DOI: 10.1063/1.361898
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic and thermodynamic properties of Sr2LaFe3O9

Abstract: Articles you may be interested inThe manipulation of magnetic properties by resistive switching effect in CeO2/La0.7(Sr0.1Ca0.9)0.3MnO3 system J. Appl. Phys. 113, 17C708 (2013); 10.1063/1.4795214Effect of (Bi, La)(Fe, Zn)O3 thickness on the microstructure and multiferroic properties of BiFeO3 thin films Measurements of the magnetization, specific heat, and 57 Fe Mössbauer spectrum are presented for Sr 2 LaFe 3 O 9 . The temperature dependence of the specific heat and magnetization indicates that Sr 2 LaFe 3 O … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
6
0

Year Published

1997
1997
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 13 publications
2
6
0
Order By: Relevance
“…This behavior is also reflected in the magnetic susceptibility, which exhibits a sharp jump at the transition, in agreement with the susceptibility measured by Wang et al [4] and also with the one reported by Zhou et al [3], see figure 3. We see that the susceptibility curve obtained within the mean-field theory fits both qualitatively and quantitatively to the one measured by Wang et al [4], however the authors of ref. [3] obtain a larger jump at the critical temperature.…”
Section: Resultssupporting
confidence: 80%
See 3 more Smart Citations
“…This behavior is also reflected in the magnetic susceptibility, which exhibits a sharp jump at the transition, in agreement with the susceptibility measured by Wang et al [4] and also with the one reported by Zhou et al [3], see figure 3. We see that the susceptibility curve obtained within the mean-field theory fits both qualitatively and quantitatively to the one measured by Wang et al [4], however the authors of ref. [3] obtain a larger jump at the critical temperature.…”
Section: Resultssupporting
confidence: 80%
“…On the other hand, the compound with the closest composition to the latter was studied experimentally by Wang et al in [4]. Therefore, we believe that our theory is more suitable for fitting the experimental data of ref.…”
Section: Resultsmentioning
confidence: 76%
See 2 more Smart Citations
“…8,9 RBFO compounds are more or less widely explored until now. [3][4][5][6][7][8][9] On the other hand for RSr 2 Fe 3 O 9 ͑RSFO͒, while the structural details are available for most of R members, 10 detailed magnetic measurements were reported recently only for LaSr 2 Fe 3 O 9 ͑LSFO͒.…”
mentioning
confidence: 99%